First Nations Children Count: An Indigenous Envelope for Quantitative Research - Blackstock, Cindy (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
Indigneous peoples have increasingly called for disaggregated data to inform policy and practice and yet there has been very little discourse on how to “Indigenenize” quantitative research. This article provides a synopsis of Indigenous research goals before moving onto describe how quantitative research can be placed in an Indigenous envelope to advance Indigenous child health and welfare policy goals.